The Evolution of the Spanish Diplomacy in the late XX - early XXI Century - E V Kosyak (Vestnik RUDN. International Relations, 2015)
At the turn of XXth century significant changes have occurred in the internal organizational structure of the Spanish Foreign Ministry’s central body and its missions abroad. Among the reasons - the consequences of further European integration, global nature of the Spanish foreign policy and expansion of national interests. In 2011-2014 takes place a reform of the Spanish Foreign Ministry’s central body. The most significant foreign affairs-related documentation has been approved, among which - the Law on foreign policy activities and Diplomatic Service. The approval and acceptance of these documents leads to fill the legal vacuum in the field of foreign policy regulation, as well as restructures the organizational structure of the Ministry of Foreign Affairs in accordance with dictates of the time and the extended foreign policy agenda.